Design and Develop an Autonomous UAV Airship for Indoor Surveillance and Monitoring Applications - Hairol Nizam Mohd Shah; Mohd Zamzuri Ab Rashid; Zalina Kamis; Mohd Shahrieel Mohd Aras; Nursabillilah Mohd Ali; Faizil Wasbari; Mohd Nor Fakurazy Bin Abu Bakar (JOIV : International Journal on Informatics Visualization, 2018)
This project is about to develop an airship based on small size remotely controlled by human. The airship is one of Unmanned Airship Vehicle (UAV) which is can be apply in advertising, VIP security inspection, traffic monitoring and management and so on. The main purpose of this project is to design and develop an autonomous UAV airship for indoor surveillance and monitoring applications. The image will be captured from wireless camera where it mounted at a bottom of gondola. To determine the centroid points of the object are implemented in three phase edge detector, canny operator and threshold. The object will be display on Graphical User Interface (GUI) in 2D coordinated. In this project the systems able to detect only one object at one time.